Aβ-induced vulnerability propagates via the brain’s default mode network - Tharick A. Pascoal (Nature Portfolio, 2019)
Amyloid-β (Aβ) deposition occurs in Alzheimer's disease but its relation to disease features such as local brain hypometabolism or cognitive decline is unclear. Here, the authors show that Aβ aggregation in the brain’s default mode network leads to hypometabolism in distant but functionally connected areas.